Security concern based Damgard-Jurik algorithm for data transmission in decentralized cloud storage - Karuppasamy Lakshmanan; Vasudevan Venkatraman (Institute of Advanced Engineering and Science, 2026)
Decentralized cloud storage (DCS) provides IT resources to a growing community of users. Decentralized storage systems offer availability, redundancy, and security because the data will be spread across numerous nodes. Despite its benefits, there are still challenges associated with DCS, such as inconsistency in data versions, complicated data retrieval, and the problem of data integrity and privacy. To effectively handle these challenges, it is necessary to come up with new solutions. To overcome these issues, a novel Dual-Chunk redundancy assisted Damgard-Jurik-incorporated slice-based data security (DRAGO-SLICE) framework has been suggested in this paper to improve security and reliability in DCS. The suggested approach utilizes the Damgard-Jurik algorithm (DJA) for encrypting the cloud resource data. The slicing process divides encrypted data into multiple chunks to increase security. Enhanced system reliability has been achieved by implementing dual chunk redundancy (DCR). Python has been used to simulate the suggested model. The efficacy of the developed approach is evaluated utilizing metrics namely decryption time (DT), security strength, encryption time (ET), latency, computational overhead, reliability, storage efficiency, and throughput. The proposed DRAGO-SLICE strategy performs better in terms of security than the existing methods, including Ethereum virtual machine elliptic-curve cryptography (EVM-ECC), decentralized blockchain-based security (DeBlock-Sec), and blockchain-based decentralized storage system (BC-DSS) approaches, by 21.05%, 13.74%, and 8.52%, respectively.